Improvement of process and equipment for homogenization of components of soft pharmaceutical dosage forms - Marchenko, Oleksandr; Hrininh-Hera, Kateryna; Omelianenko, Kostiantyn; Gubenia, Oleksii (My University, 2024)
Research was conducted to improve the process of homogenization of the components of soft pharmaceutical dosage forms and cosmetic products. The scientific novelty of the results is to obtain a number of dependences of the viscosity of ointments and pastes on the shear rate and temperature. The practical value is to improve the design of the homogenizer and, accordingly, to reduce the time of homogenization.
Keywords: гомогенізатор; homogenizer; гомогенізація лікарських форм; homogenization of dosage forms; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра мехатроніки та пакувальної техніки